Recurrent de novo missense variants in GNB2 can cause syndromic intellectual disability. Issue 5 (28th June 2021) - Tan, Natalie B; Pagnamenta, Alistair T; Ferla, Matteo P; Gadian, Jonathan; Chung, Brian HY; Chan, Marcus CY; Fung, Jasmine LF; Cook, Edwin; Guter, Stephen; Boschann, Felix; Heinen, Andre; Schallner, Jens; et al.
Abstract : Purpose: Binding proteins (G-proteins) mediate signalling pathways involved in diverse cellular functions and comprise Gα and Gβγ units. Human diseases have been reported for all five Gβ proteins. A de novo missense variant in GNB2 was recently reported in one individual with developmental delay/intellectual disability (DD/ID) and dysmorphism. We aim to confirm GNB2 as a neurodevelopmental disease gene, and elucidate the GNB2 -associated neurodevelopmental phenotype in a patient cohort. Methods: We discovered a GNB2 variant in the index case via exome sequencing and sought individuals with GNB2 variants via international data-sharing initiatives. In silico modelling of the variants was assessed, along with multiple lines of evidence in keeping with American College of Medical Genetics and Genomics guidelines for interpretation of sequence variants. Results: We identified 12 unrelated individuals with five de novo missense variants in GNB2, four of which are recurrent: p.(Ala73Thr), p.(Gly77Arg), p.(Lys89Glu) and p.(Lys89Thr). All individuals have DD/ID with variable dysmorphism and extraneurologic features. The variants are located at the universally conserved shared interface with the Gα subunit, which modelling suggests weaken this interaction. Conclusion: Missense variants in GNB2 cause a congenital neurodevelopmental disorder with variable syndromic features, broadening the spectrum of multisystem phenotypes associated with variants in genes encoding G-proteins.